Pelatihan Instagram Bisnis Pengusaha Muda Desa Tumbrep Kabupaten Batang - Rukti Rumekar; Mj Rizqon Hasani; Ropinov Saputro; Erika Celindia; Heru Anisa Agustiani; Ageng Prathama, Nikolaus (Jurnal Atma Inovasia, 2023)
This service activity related to Instagram business training for young entrepreneurs was carried out in Tumbrep Village, Bandar District, Batang Regency. The purpose of this service is to provide additional knowledge for young entrepreneurs who use a digital approach in carrying out their business activities, especially Instagram. The methods used are observation and interviews, presentation of material or lectures, focus group discussions and technical training, exhibitions or MSME bazaars. At first, the young entrepreneurs from Tumbrep Village still managed personal Instagram accounts for personal and business activities. In addition, the results of posting photos are still not conceptualized. Through community service activities, participants are invited to take advantage of Instagram for business and edit product photos to be posted. The conclusion from this service is that managing Instagram accounts for business activities requires special concepts and techniques. The training conducted by the service team who has this competence is really needed by the young entrepreneurs of Tumbrep Village.